Ion beam engineered graphene oxide membranes for mono-/di-valent metal ions separation. (March 2020) - Wei, Yibin; Pastuovic, Zeljko; Shen, Chao; Murphy, Timothy; Gore, Damian B.
Abstract: Graphene oxide (GO) membranes with precisely controlled nanopores are promising for selectively ionic separation. Here, an ion beam was used to efficiently and simply post-modify GO membranes, creating nanopores in a controllable manner. We compared the influence of GO membrane thickness and ion fluence on the GO structure and the consequent mono-/di-valent metal ion separation performance. Experimental results indicate all GO membranes exhibited improved K + selectivity with respect to other ions after ion beam irradiation. Moreover, the K + ion permeability of the optimal membranes is up to 1.4 × 10 −3  mol m −2  h −1 and the membrane shows extremely high K + separation factor to di-valent ions. Remarkably, this method could be used as an in-situ post-treatment for pre-assembled GO membranes. We believe that this strategy offers novel insights into fabricating nanoporous membranes constructed by two-dimensional nanomaterials for a variety of fields including energy, desalination and biomedical applications. Graphical abstract: Image 1